A relevant exposure to a food matrix contaminated environmentally by polychlorinated biphenyls induces liver and brain disruption in rats. (October 2016) - Ounnas, Fayçal; Privé, Florence; Lamarche, Fréderic; Salen, Patricia; Favier-Hininger, Isabelle; Marchand, Philippe; Le Bizec, Bruno; Venisseau, Anais; Batandier, Cécile; Fontaine, Eric; de Lorgeril, Michel; Demeilliers, Christine
Abstract: Polychlorinated biphenyls (PCBs) are ubiquitous environmental contaminants present in dietary fats. Most studies evaluating PCB effects have been conducted with a single compound or a mixture of PCBs given as a single acute dose. The purpose of this study was to evaluate in vivo PCB toxicity in a realistic model of exposure: a low daily dose of PCBs (twice the tolerable daily intake (TDI)), chronically administered (8 weeks) to rats in contaminated goat milk. Liver and brain PCB toxicities were investigated by evaluating oxidative stress status and mitochondrial function. PCB toxicity in the liver was also estimated by transaminase enzymatic activity. This study shows that even at low doses, chronic PCB exposure resulted in a statistically significant reduction of mitochondrial function in liver and brain. In the liver, oxygen consumption in the condition of adenosine triphosphate (ATP) production (state 3) decreased by 22–29% ( p  < 0.01), according to the respiratory substrates. In the brain, respiratory chain complexes II and III were reduced by 24% and 39%, respectively ( p  < 0.005). The exposed rats presented higher lipid peroxidation status (+20%, p  < 0.05) and transaminase activity (+30%, p  < 0.05) in the blood. Thus, our study showed that exposure of rats to a daily realistic dose of PCBs (twice the TDI in a food complex mixture of environmental origin) resulted in multiple disruptions in the liver and brain. Highlights: A relevant animal model (daily low dose, mixture of PCBs). A dietary environmentally PCBs contaminated matrix. At low doses, chronic PCBs exposure resulted in adverse effects in liver. At low doses, chronic PCBs exposure resulted in adverse effects in brain. Understanding on mechanisms of PCBs toxic effects which involve mitochondria.